Gambaran persepsi hambatan pasangan serodiskordan dalam perilaku pencegahan penularan HIV/AIDS di Surabaya - Valuvi, Cahyaning Hendri (Journal of Health Education and Literacy, 2022)
Background : Human Immunodeficiency Virus (HIV) is a virus who can attacks immune system’s cells, which help body respond to infection. Without effective treatment, HIV can develop into Acquired Immunodeficiency Syndrome (AIDS). Based on age, the higest population of HIV’s transmission are the groups of 25-49 years old (prevalence 71.3%) and 20-24 years old (prevalence 16.3%), which means that the most cases of HIV / AIDS transmission occur in woman’s reproductive age. In the reproductive age, woman may decide to marry, become a housewife, have a sex and pregnant. Some of housewife in Surabaya have an HIV-positive couple (serodiscordant couple). The prevention behavior of HIV/AIDS transmission should be done by serodiscordant couple because a husband can transmit HIV to his wife, and wife can transmit HIV to their child. Health Belief Model (HBM) is a model which can describe someone’s health behaviors in preventive behaviors and uses health services. One of component in Health Belief Model is perceived barriers. Methods : This research is qualitative research: phenomenology research. Data was collected by in-depth interview. The Health Belief Model components’ which is used in this research was perceived barriers. Result : Every serodiscordant couple have their own perceived barriers to their illness. Some of perceived barriers whom found in this research were side effect of treatments, treatment initiation, treatment schedule, and condom initiation Conculusion : Partiscipants’perceived barriers effect on their preventive behaviour of HIV/AIDS transmission.